Digital lives in psychotherapy: 'the other in the room'. Issue 2 (3rd April 2017) - Kingsley, Marc J.; Stockmann, Tom; Wright, Daniel
Abstract : Within the broader area of digital risk, there has been concern over the phenomena of 'cyber suicide', a completed or attempted suicide influenced by the internet. We propose a theoretical explanation of the 'ambivalent self' in people who go online searching for suicide, by introducing the concept of an inner split between the 'suicidal part' (SP) and 'non-suicidal part' (NSP) within the personality structure of the individual which struggle for domination of the inner life and external relationships and decisions of the suicidal person. This is grounded in psychoanalytic theory and draws upon a broader conceptualisation of the psyche of the self as split between rival parts, and differing states of mind, competing for control of the vulnerable individual and their capacity to tolerate and manage emotional pain and reality. The recognition and awareness of an inner split between the SP and NSP of the person who goes online, and how this influences virtual relationships, as well as external relationships, such as in psychotherapy, is an important understanding for contemporary psychotherapy and risk management in the digital age.